The Puzzle of Perceptual Justification Conscious experience, Higher-order Beliefs, and Reliable Processes - Ghijsen, Harmen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides an accessible and up-to-date discussion of contemporary theories of perceptual justification that each highlight different factors related to perception, i.e., conscious experience, higher-order beliefs, and reliable processes. The book$1 (Bs discussion starts from the viewpoint that perception is not only one of our fundamental sources of knowledge and justification, but also plays this role for many less sophisticated animals. It proposes a scientifically informed reliabilist theory which can accommodate this fact without denying that some of our epistemic abilities as human perceivers are special. This allows it to combine many of our intuitions about the importance of conscious experience and higher-order belief with the controversial thesis that perceptual justification is fundamentally non-evidential in character.s
Chapter 1. Perception, Hallucination and Justification -- Chapter 2. Evidentialism and the Problem of Fit -- Chapter 3. Dogmatism and the Distinctiveness Problem -- Chapter 4. Epistemological Disjunctivism and Higher-Order Issues -- Chapter 5. Process Reliabilism and Its Classic Problems -- Chapter 6. A Higher-Order Rejoinder for Reliabilism.
Keywords: Epistemology; Philosophy of mind; Philosophy and science; Epistemology; Philosophy of Mind; Philosophy of Science